Lecithin addition to starter pig diets with and without added fat and whey - D M Van Wormer; D S Pollmann (Kansas Agricultural Experiment Station Research Reports, 1984)
A total of 316 crossbred weanling pigs were used in two studies to evaluate the effect of the addition of edible-grade, unbleached soy lecithin on growth in starter pig diets with and without added fat and/or dried whey. Addition of fat to a corn-soybean meal diet improved (P<.05) feed efficiency but addition of lecithin did not affect performance. When lecithin and fat were added in combination, average daily gain was less (P<.05) than for diets without added fat. This may be due to a high level of undigestible fat having a limiting effect on intake and consequently decreasing gains. A low level of lecithin (1.5%) in diets without whey gave approximately the same response as a 4% fat diet without whey thus making lecithin a possible fat substitute should, it be economically feasible.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Lecithin; Swine; Fat; Whey; Starter pig